A computational analysis of local flow for reacting Diesel sprays by means of an Eulerian CFD model. (February 2018) - Pandal, A.; García-Oliver, J.M.; Novella, R.; Pastor, J.M.
Highlights: ∑-Y Eulerian model has been coupled with the Approximated Diffusion Flamelet model. Accurate predictions at quasi-steady flame conditions are provided by the model. Reacting entrainment rate drop upstream LoL is due to low temperature reaction. Flow confinement does not seem to influence the global flame behaviour. Abstract: An implementation and validation of the coupled Σ-Y ADF model is presented in this work for reacting Diesel spray CFD simulations under a RANS turbulence modeling approach. An Approximated Diffusion Flamelet (ADF) model Michel et al. (2008) implemented in the OpenFOAM CFD open-source library by Winklinger (2014) is fed with the spray description, i.e. mixing formation process, provided by the Σ-Y Eulerian atomization model Garcia-Oliver et al. (2013). In the present investigation, the Engine Combustion Network Spray A reference configuration is used for validation. Specifically, the model can provide accurate predictions of typical reacting spray metrics, such as the ignition delay and the lift-off length. Moreover, the internal structure is also fairly reproduced in terms of quasi-steady spatial distribution of formaldehyde and OH, related with low and high temperature reactions respectively. Additionally, modeling results have been compared to recent Particle image velocimetry (PIV) measurements Garcia-Oliver et al. (2017) under both inert and reacting conditions. Flow response to heat release is quantitatively predicted by the model, both in terms of local velocity increase as well as radial dilation. The model has been used to understand combustion-induced reduction in entrainment, in particular around the lift-off length location. Flow confinement does not seem to influence the global flame behaviour, even though some changes in the local flow hint can be observed when moving from an open to a closed domain.